2011
DOI: 10.1038/nm.2330
|View full text |Cite
|
Sign up to set email alerts
|

GIT1 is associated with ADHD in humans and ADHD-like behaviors in mice

Abstract: Attention deficit hyperactivity disorder (ADHD) is a psychiatric disorder that affects ~5% of school-aged children; however, the mechanisms underlying ADHD remain largely unclear. Here we report a previously unidentified association between G protein-coupled receptor kinase-interacting protein-1 (GIT1) and ADHD in humans. An intronic single-nucleotide polymorphism in GIT1, the minor allele of which causes reduced GIT1 expression, shows a strong association with ADHD susceptibility in humans. Git1-deficient mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
166
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(187 citation statements)
references
References 59 publications
18
166
3
Order By: Relevance
“…The neurobehavioral defects of ACC mice are very similar to defects described in ADHD mouse models, including DAT knockout or knockdown mice (4), GIT1 (G protein-coupled receptor kinase-interacting protein-1) knockout mice (31), or mice overexpressing casein kinase 1-δ (CK1δ) (27). Associative learning was impaired in DAT and GIT1 mutants (31,45), and anxiety was reduced in CK1δ-overexpressing mice (27), similar to what we reported previously for n-cofilin mutants (19,20). The behavioral abnormalities in ACC mice include all hallmarks of ADHD, suggesting that ACC mice are a valuable tool to study the mechanisms underlying ADHD.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The neurobehavioral defects of ACC mice are very similar to defects described in ADHD mouse models, including DAT knockout or knockdown mice (4), GIT1 (G protein-coupled receptor kinase-interacting protein-1) knockout mice (31), or mice overexpressing casein kinase 1-δ (CK1δ) (27). Associative learning was impaired in DAT and GIT1 mutants (31,45), and anxiety was reduced in CK1δ-overexpressing mice (27), similar to what we reported previously for n-cofilin mutants (19,20). The behavioral abnormalities in ACC mice include all hallmarks of ADHD, suggesting that ACC mice are a valuable tool to study the mechanisms underlying ADHD.…”
Section: Discussionmentioning
confidence: 87%
“…Maintenance of the E/I balance is crucial for the functionality of the brain (49), and E/I imbalance is postulated to underlie the pathogenesis of neuropsychiatric disorders, such as autism, schizophrenia or Tourette's syndrome (50)(51)(52). More recent studies have associated E/I imbalance with ADHD (31,(53)(54)(55). In these studies, it is suggested that reduced neuronal inhibition contributes to ADHD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulldown of GIT or PIX quantitatively captures the other partner . GIT and PIX appear unstable when not in a complex because T-cells of α-PIX-deficient mice have reduced levels of GIT2 (Missy et al, 2008), GIT1-deficient mice have reduced levels of PIX in the brain (Won et al, 2011) and GIT2-deficient mice have reduced levels of PIX in immune organs (Hao et al, 2015). Nevertheless, despite clear evidence that GIT and PIX are tightly associated and function together, many publications continue to report on GIT or PIX proteins individually, ignoring potential involvement of the other partner.…”
Section: Git Proteinsmentioning
confidence: 99%
“…Indeed, Cat-1 has recently been implicated in stimulating neuronal synaptic activity (11) and dendritic spine formation (12,13), as well as in inducing T-cell activation (14). Moreover, Cat-1 has been implicated in attention deficit hyperactivity disorder and in Huntington disease (15,16).…”
mentioning
confidence: 99%